Using NanoSIMS to map trace elements in stainless steels from nuclear reactors - Lozano-Perez, S; Schröder, M; Grovenor, C; Yamada, T; Terachi, T; English, C (2008)
A Cameca NanoSIMS 50 has been used to map trace elements in stainless steels from nuclear reactors. The results prove that it is an ideal technique to map elements in small concentrations such as boron, sulphur or phosphorous which remain inaccessible to conventional microanalysis techniques. Especially remarkable is the ability to map boron, revealing segregation to grain boundaries or to carbides in sensitized samples. © 2008 Elsevier B.V. All rights reserved.